Inhibition of xanthine oxidase ameliorates functional and metabolic impairment in type 2 diabetic hearts under pressure overload. (25th November 2020) - Igaki, Y; Osanami, A; Tanno, M; Sato, T; Ogawa, T; Yano, T; Kouzu, H; Miura, T
Abstract: Background: We recently reported that upregulated AMP deaminase (AMPD), via reduction in the tissue adenine nucleotide pool, contributes to exacerbation of diastolic dysfunction under pressure overload in OLETF, a rat model of obese type 2 diabetes (T2DM). Upregulated AMPD also possibly promotes xanthine oxidase (XO)-mediated ROS production, since AMPD deaminases AMP to IMP, which is further converted to inosine, providing substrates of XO, hypoxanthine and xanthine. Here, we examined the hypothesis that inhibition of XO ameliorates the pressure overload-induced diastolic dysfunction by suppression of ROS-mediated mitochondrial dysfunction and/or vascular dysfunction in T2DM rats. Methods and results: Metabolomic analyses revealed that levels of xanthine and uric acid in the LV myocardium were significantly higher by 37% and 51%, respectively, in OLETF than in LETO, non-diabetic control rats, under the condition of phenylephrine-induced pressure overloading (200–230 mmHg). Myocardial XO activity in OLETF was 57.9% higher than that in LETO, which may be attributed to 31% higher level of inosine, a positive regulator of XO, in OLETF than in LETO. The activity of XO was significantly attenuated by administration of topiroxostat, an XO inhibitor at 0.5 mg/kg/day for 14 days. Pressure volume loop analyses showed that the pressure overloading resulted in significantly higher LVEDP in OLETF than in LETO (18.3±1.5 vs. 12.2±1.3 mmHg, p<0.05, n=7), though LVEDPs at baseline were comparable in OLETF and LETO (5.6±0.4 vs. 4.7±0.7 mmHg). Treatment with topiroxostat significantly suppressed the pressure overload-induced elevation of LVEDP in OLETF (18.3±1.5 vs. 11.3±1.1 mmHg, p<0.05) but not in LETO. Under the condition of pressure overloading, Ea/Ees, an index for ventricular-arterial coupling, was higher in OLETF than in LETO (2.3±0.3 vs. 1.6±0.3, p<0.05), and it was also improved by topiroxostat in OLETF (1.2±0.2, p<0.05). Myocardial ATP content was lower in OLETF than in LETO (2966±400 vs. 1818±171 nmol/g wet tissue, p<0.05), and treatment with topiroxostat significantly restored the ATP level (2629±307 nmol/g wet tissue). The LV myocardium of OLETF under pressure overload showed significantly higher level of malondialdehyde and 4-hydroxynonenal, an indicator of lipid peroxidation, than that of LETO. Measurement of oxygen consumption rate by Seahorse XFe96 Analyzer in mitochondria isolated from LV tissues revealed that state 3 respiration was significantly suppressed in OLETF by 43% compared to LETO, and it was restored by treatment with topiroxostat. Conclusion: Both activity and substrates of XO are increased in T2DM hearts, in which upregulation of AMPD may play a role. Inhibition of XO ameliorates pressure overload-induced diastolic dysfunction and improves ventricular-arterial coupling in diabetic hearts, most likely through protection of mitochondrial function from ROS-mediated injury. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Grant-in-aid for Scientific Research (#26461132, #17K09584) from the Japanese Society for the Promotion of Science